Local Wisdom-Based E-Module with Project-Based Learning Model: Enriching Energy Topic in Physics Learning - Widayanti, Widayanti; Sinensis, Arini Rosa; Firdaus, Thoha; Effendi, Effendi; Sholikahah, Ainun Ummi (Indonesian Journal of Science and Mathematics Education, 2022)
The module is one of the supporting teaching materials that can be developed according to learning needs. The purpose of this research is to develop an e-module based on the local wisdom of Belitang with a project-based learning model. The physics topic used is Energy at the junior high school level. The development design used is a modification of the ADDIE model (analyze, design, development, implementation, evaluation). However, this research only reached the development stage because the focus research was only on developing e-modules. The instrument used for data collection is a questionnaire with a Likert scale and analyzed descriptively quantitatively. Research findings show that e-modules based on Belitang local wisdom with a project-based learning model get media and content validation values in the very good category. The results of this research are expected to be further applied to learning.